1960
DOI: 10.3382/ps.0390144
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Inheritance and Age of Hen upon Initial Egg Quality

Abstract: 1955. Paper electrophoresis as a quantitative method. Biochem. J. 60: 205-21S. Kumaron, J. D. S., and C. W. Turner, 1949. The endocrinology of spermatogenesis in birds. III. Effect of hypo-and hyperthyroidism. Poultry Sci. 28: 653-655. MacKenzie, C. G., and J. B. MacKenzie, 1943.Effect of sulphonamides and thioureas on the thyroid gland and basal metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

1967
1967
1970
1970

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
3
0
1
Order By: Relevance
“…Henderson et al (1941), Geake (1958, 1960) and Jenkins and Taylor (1960) have demonstrated that there is a high degree of variability in shell quality from bird to bird. Henderson et al (1941), Geake (1958, 1960) and Jenkins and Taylor (1960) have demonstrated that there is a high degree of variability in shell quality from bird to bird.…”
Section: Shell Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Henderson et al (1941), Geake (1958, 1960) and Jenkins and Taylor (1960) have demonstrated that there is a high degree of variability in shell quality from bird to bird. Henderson et al (1941), Geake (1958, 1960) and Jenkins and Taylor (1960) have demonstrated that there is a high degree of variability in shell quality from bird to bird.…”
Section: Shell Qualitymentioning
confidence: 99%
“…The literature concerning the nature of these relationships has been reviewed by Johnson and Merritt (1955), Funk et al (1958), Cunningham et al (1960), Taylor (1960) and Bornstein and Lipstein (1962). The literature concerning the nature of these relationships has been reviewed by Johnson and Merritt (1955), Funk et al (1958), Cunningham et al (1960), Taylor (1960) and Bornstein and Lipstein (1962).…”
mentioning
confidence: 99%
“…-effect on nutrient composition of chicken eggs is limited (Taylor, 1960). Jackson et al (1946), Asenjo (1950), Arroyave et al (1957) and Mayfield et al (1955) compared riboflavin levels in eggs from various breeds.…”
Section: R Esearch Indicating An Hereditarymentioning
confidence: 98%
“…Качество яиц зависит от возраста и породности кур, сезонности, условий кормления и содержания. Обзор литературы по этому вопросу содержится в работах ряда авторов (Johnson, Merritt, 1955;Fimk и др., 1958;Cunningham и др., 1960;Taylor, 1960;Bornstein, Lipstein, 1962 и др. ).…”
unclassified